2020
DOI: 10.2147/ndt.s267307
|View full text |Cite
|
Sign up to set email alerts
|

<p>Post-Traumatic Stress Disorder and Associated Factors Among Internally Displaced People in South Ethiopia: A Cross-Sectional Study</p>

Abstract: Background: Displaced people experience different traumatic events. This can have serious and long-lasting consequences in terms of physical and mental health outcome. Posttraumatic stress disorder (PTSD) is the most frequent mental disorder following traumatic exposure. In 2018 Ethiopia saw the highest number of internal displacement, despite this, less attention has been given to mental health among internally displaced people in the country. This study aims to determine the estimated prevalence and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
72
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 50 publications
18
72
7
Order By: Relevance
“…1.60-7.79; p=0.002). This nding is consistent with other studies which found signi cant correlation between poor mental health outcome and cumulative trauma exposure (11,(30)(31)(32)(33)…”
Section: Associations Of Sociodemographic Factors With Ptsd and Depressionsupporting
confidence: 93%
“…1.60-7.79; p=0.002). This nding is consistent with other studies which found signi cant correlation between poor mental health outcome and cumulative trauma exposure (11,(30)(31)(32)(33)…”
Section: Associations Of Sociodemographic Factors With Ptsd and Depressionsupporting
confidence: 93%
“…Common predictors of mental disorders among IDP populations are female gender ( Makhashvili et al., 2014 ; Thapa and Hauff, 2005 ; Richards et al., 2011 ; Roberts et al., 2008 ; Sheikh et al., 2015 ; Turnip and Hauff, 2007 ; Madoro et al., 2020 ) (although male gender is strongly associated with harmful alcohol use ( Ramachandran et al., 2019 ; Roberts et al., 2011 ; Roberts et al., 2014 ; Lagos-Gallego et al., 2017 ; Kizza et al., 2012 ) and experiencing multiple traumatic events ( Amodu et al., 2020 ; Makhashvili et al., 2014 ; Richards et al., 2011 ; Porter and Haslam, 2005 ; Roberts et al., 2008 ; Madoro et al., 2020 ; Gichunge et al., 2020 ; Almedom et al., 2005 ; Araya et al., 2007 ), unemployment and impoverishment ( Makhashvili et al., 2014 ; Roberts et al., 2008 ; Sheikh et al., 2015 ; Siriwardhana et al., 2013 ), and prolonged and multiple internal displacement ( Makhashvili et al., 2014 ; Siriwardhana et al., 2014 ; Madoro et al., 2020 ; Gichunge et al., 2020 ; Siriwardhana et al., 2013 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…These are preexisting factors such as mental illness and drug use in the family, the traumatic event itself, level of exposure, and post-trauma factors such as social support. 12 Individuals suffering from PTSD have the potential to influence public and mental health outcomes in several ways next to large number of immediate direct casualties in combatants and civilians. 7,10,13 It is also associated with substantial psychiatric comorbidity, 14 increased risk of suicide, and considerable economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Ethiopia on an internally displaced community reported the prevalence of PTSD to be 58.4%. 12 Another community-based cross-sectional study conducted in Ethiopia among Koshe landslide survivors showed that the prevalence of PTSD was 37.3%. 35 There are several factors associated with the occurrence of post-traumatic stress disorder following exposure to traumatic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation